An Integrity Monitoring Algorithm for GNSS Satellite Atomic Clocks. (2nd November 2019) - Huang, X.M.; Zhao, X.; Li, J.Y.; Zhu, X.W.; Ou, G.
Abstract : An algorithm for Global Navigation Satellite System satellite atomic clock integrity monitoring based on an extended measurement model is proposed. A detection statistic achieved by parity transformation is used to detect clock anomalies, and the concept of the optimal accumulation number, with a method to find it, is provided. Numerical simulations are adopted to verify the validity of detecting two typical anomalies.